Assistance In Improving The Quality Of Teacher Teaching Through Observation Of Student Learning Types: PENDAMPINGAN PENINGKATAN MUTU PENGAJARAN GURU MELALUI OBSERVASI TIPE BELAJAR SISWA - Laila, Itsna Noor; Nurul Arifin, Arofatul Muawanah , Ja’far , M.Syaikhuddin , (PUSAT PUBLIKASI ILMIAH SEKOLAH TINGGI AGAMA ISLAM (STAI) AL-YASINI PASURUAN, 2024)
This Community Service (PkM) aims to provide education and training to improve the quality of teacher teaching in dealing with developments in the era of disruption, so as to produce professional human resources in the field of education. The PkM method used is participatory action research (PAR). The result of this PkM activity is to provide benefits for class teachers in determining effective and efficient learning methods by knowing the type of student learning first. This effort was made to improve the quality of teacher teaching. PkM also provides benefits for education staff in supporting and helping educators improve the quality of teaching in the classroom. PkM activities are able to increase the knowledge, understanding, and competence of school principals, teachers, and other education personnel in realizing quality teaching as a measure to improve education quality.